The UNESCO Heritage of the Aeolian Islands (Italy) Tourism, Sustainable Development and Territorial Management - Cusumano, Mariaclaudia; Ingrassia, Marco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
Tourism represents one of the fastest-growing socio-economic sectors of our time. The Aeolian Islands are positioned in a strategic area of the southern Tyrrhenian Sea in Italy. The Archipelago of the Aeolian islands consists in seven small villages, focal points of a landscape stratified over time. These are particularly fragile and vulnerable socio-ecological systems for which it is necessary to ensure Sustainable Tourism that allows for the conservation of biodiversity, the protection of the land, and the enjoyment of the Natural Heritage for future generations.The Archipelago, in the last seventy years, has become a particularly attractive area; at the beginning, it was the cinematography, and then the inscription of the UNESCO World Heritage List occurred in 2000 to increase the popularity of the islands.Tourism flow accelerates the anthropic pressure on the territory and, if exercised systematically and uncontrolled, may incur over-tourism, causing irreversible damage to natural and social systems.This contribution aims to investigate how UNESCO branding has impacted the Archipelago. This contribution is based on the hypothesis that UNESCO recognition has accelerated the global notoriety of the islands, contributing to anthropogenic pressure factors that threaten the balance of territorial and social systems. The contribution is structured through the following research questions: (i) What are the main factors contributing to the visibility of the Aeolian islands and their identification as a tourist destination? Has the inscription in the WHL represented a pull factor favoring an increase or a typological variation of tourist flows? (ii) Does the WHL inscription favor adequate management of the Aeolians Islands as a strategy to preserve the Outstanding Natural value? (iii) Has the inscription in the WHL contributed to promoting Sustainable Development for the Socio-economic and Territorial system at the local level, as prescribed the Agenda 2030 for Sustainable Development Goals of the UN? This research shows a constant and increasing anthropogenic load on the Archipelago, which in the peak season registers the exceeding of the carrying capacity due to the partial application of the prescriptions provided by the Management Plan and the failure to update it. The UNESCO Heritage Management Plan, through the identification of spatial planning and management tools, should contribute to the achievement of sustainability on the local level and thus to the achievement of SDGs on the global level. The results showed that the increase in tourism in the Aeolian Islands aligns with the Sicilian region data, so the inscription in the WHL impacted the visibility of the Archipelago only partially. However, there is an increasing tourist trend, as in fragile areas and small villages with limited carrying capacity, over-tourism will shortly impact the heritage ecosystem of small towns. It is necessary to make a joint effort among public and private bodies to ensure the Sustainability of the Aeolian Islands in the light of promoting Sustainable Tourism. Limits of this research consisted of having analyzed partially tourist data on tourism, for instance, the lack of data related to: marine traffic; difficulties in monitoring the number of boats and yachts effectively. difficulties in calculating effectively the number of tourists in the Archipelago that spend nights on the boats and yachts; iii. difficulties in tracking passengers of daily cruises, which elude the official data recorded.